A cohort study of 49 933 women with surgically verified endometriosis: Increased incidence of breast cancer below the age of 40. (8th April 2019) - Saavalainen, Liisu; Lassus, Heini; But, Anna; Tiitinen, Aila; Härkki, Päivi; Gissler, Mika; Pukkala, Eero; Heikinheimo, Oskari
Abstract: Introduction: The association between endometriosis and breast cancer is unclear. We assessed the risk of breast cancer in women with surgically verified endometriosis, with special focus on the age at cancer diagnosis, time from endometriosis diagnosis and breast cancer histology. Material and methods: All women with first endometriosis‐associated diagnoses occurring concomitantly with relevant surgical codes during 1987‐2012 were retrieved from the Finnish Hospital Discharge Register in Finland. Breast cancers diagnosed after the endometriosis diagnosis were identified from the Finnish Cancer Registry. The Finnish female population served as the reference. The endometriosis cohort consisted of 49 933 women (23 210 cases of ovarian, 20 187 peritoneal and 2372 deep infiltrating endometriosis). The outcome measure was the standardized incidence ratio (SIR) with 95% confidence interval (95% CI) of breast cancer calculated for the whole cohort and for the subtypes of endometriosis, stratified by the age at breast cancer diagnosis, histology and time from endometriosis diagnosis. Results: The overall risk of breast cancer (1555 cases) was similar to the reference population (SIR 0.99; 95% CI 0.94‐1.03), did not differ in types of endometriosis, and was similar for ductal and lobular breast cancer. However, the SIR of breast cancer was increased in the age group of 20‐29 years (SIR 4.44; 95% CI 2.22‐7.94) and in the age group of 30‐39 years (SIR 1.28; 95% CI 1.03‐1.57). The risk of in situ breast cancer (170 cases) was increased in the entire endometriosis cohort (SIR 1.25; 95% CI 1.07‐1.44). Conclusions: The overall risk of breast cancer in women with surgically verified endometriosis was similar to that of general population. However, the risk of breast cancer at young age was increased. Young women with surgically verified endometriosis represent highly symptomatic patients with more frequent surgeries and additional therapies that might also contribute to the risk of breast cancer.